2020
DOI: 10.20527/jps.v7i1.8087
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Fisika Sediaan Suspensi Ekstrak Etanol Daun Gaharu (Aquilaria microcarpa Baill.) dengan Variasi Carboxymethyl Cellulose Sodium (CMC-Na)

Abstract: ABSTRAK Gaharu (Aquilaria microcarpa Baill.) merupakan salah satu hasil hutan yang memiliki aktivitas antioksidan. Ekstrak etanol daun A. microcarpa terbukti memiliki aktivitas antioksidan yang tergolong sangat aktif. Ekstrak etanol daun A. microcarpa kemudian dibuat menjadi sediaan suspensi dengan variasi CMC-Na sebagai agen pengsuspensi. Penelitian ini bertujuan untuk menentukan pengaruh konsentrasi CMC-Na terhadap karakteristik fisik suspensi ekstrak etanol daun A.microcarpa. Suspensi dibuat dengan variasi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Stenochlaena palustris herb was sorted in wet sorting and washed thoroughly with running water so that dirt does not stick. It was stretched and dried using an oven with a 55 ± 2°C temperature to dry 16 . Simplisia was then preoccupied and sifted with a mesh sieve 20.…”
Section: Preparation Of Simpliciamentioning
confidence: 99%
“…Stenochlaena palustris herb was sorted in wet sorting and washed thoroughly with running water so that dirt does not stick. It was stretched and dried using an oven with a 55 ± 2°C temperature to dry 16 . Simplisia was then preoccupied and sifted with a mesh sieve 20.…”
Section: Preparation Of Simpliciamentioning
confidence: 99%
“…Setelah itu suspensi CMC dipindahkan ke beaker glass 100 mL, volumenya dicukupkan dengan aquadest hingga 100 mL. Suspensi CMC 0,5% diberikan secara oral pada tikus putih jantan berdasarkan berat badan masing-masing tikus (Fitriana et al, 2020).…”
Section: Pembuatan Suspensi Bahan Pembuatan Suspensi Cmc 05%unclassified
“…All parts of the noni can be used as medicinal plants, such as flowers, leaves, bark, stems, roots, and fruits [8]. Several studies have reported the part of plants (seeds, fruits, leaves, and root bark) used as antioxidants, analgesics, hypoglycemic, anti-inflammatory, and anti-cancer [9].…”
Section: Introductionmentioning
confidence: 99%